A case study on the implementation of blended learning education: Stakeholders' views - Ezzatlo, Nada (AUC Knowledge Fountain, 2020)
An Egyptian school for further education affiliated to a higher education institution, offered a blended learning course for continuing education learners. However, it was decided after the first week, that the planned blended courses would proceed but through using flipped learning technique. In addition, the instructors would attend professional development training on implementing blended learning prior to the following term. Accordingly, a qualitative study was conducted to understand the implementation of blended learning addressed and to know the views on the effectiveness of the professional development training sessions delivered to the blended learning instructors. Semi-structured interviews were conducted with 17 participants. The theoretical frameworks used in this case study are the community of inquiry by Garrisons (2017), and the diffusion of innovations by Rogers, (2003). In addition, the data was analyzed through content analysis where themes were identified to answer the following questions; 1. How was blended learning education diffused as an educational innovation at University Y and at the Further Education School?; 2.What are the stakeholder’s views regarding the implementation of blended learning education at the Further Education School?; 3. What are the participant’s views on the relevance of the professional development training facilitated to the instructors to address their needs? The results revealed the process of and the views on diffusing blended learning in the university till it reached its’ affiliation. The instructors’ shared areas of satisfactions and areas of concerns regarding the relevance of the professional development training they attended were identified. The findings may aid higher education institutions in understanding the vitality of professional development and the reasons for success and failure in implementing new educational innovation.